2015
DOI: 10.1016/j.neuroimage.2015.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating conflict: Neural correlates of a Bayesian belief and its motor consequence

Abstract: Previous studies have examined the neural correlates of proactive control using a variety of behavioral paradigms; however, the neural network relating the control process to its behavioral consequence remains unclear. Here, we applied a dynamic Bayesian model to a large fMRI data set of the stop signal task to address this issue. By estimating the probability of the stop signal – p(Stop) – trial by trial, we showed that higher p(Stop) is associated with prolonged go trial reaction time (RT), indicating proact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
81
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 143 publications
(164 reference statements)
15
81
1
Order By: Relevance
“…The results for the current cohort showed that, across all participants, GoRT was significantly correlated with p(Stop) (r ϭ 0.9665, p ϭ 0.0000, df ϭ 112), indicating a strong sequential effect, and the stop error rate was inversely correlated with p(Stop) (r ϭ Ϫ0.9080, p ϭ 0.0000, df ϭ 112), both of which were consistent with the predictions of the Bayesian model (see Fig. 1 in Hu et al, 2015).…”
Section: Behavioral Performancesupporting
confidence: 77%
See 4 more Smart Citations
“…The results for the current cohort showed that, across all participants, GoRT was significantly correlated with p(Stop) (r ϭ 0.9665, p ϭ 0.0000, df ϭ 112), indicating a strong sequential effect, and the stop error rate was inversely correlated with p(Stop) (r ϭ Ϫ0.9080, p ϭ 0.0000, df ϭ 112), both of which were consistent with the predictions of the Bayesian model (see Fig. 1 in Hu et al, 2015).…”
Section: Behavioral Performancesupporting
confidence: 77%
“…Conflict anticipation was quantified by the probability of a stop trial computed from a Bayes optimal decision-making model, which assumes that participants choose whether to "go" on the basis of accumulating evidence. This model explained stopping behavior in the stop signal task and predicted increased stop error rate with increasing stop signal delay as well as faster stop error than correct go response time Hu et al, 2015). In combination with the imaging data, we reported that activations of righthemispheric SFG to conflict anticipation are negatively correlated with both SSRT and motor urgency.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations